2010
DOI: 10.1007/s11307-010-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of FDG–PET and PET/CT in Non-malignant Thoracic Disorders

Abstract: There have been several endeavors made to investigate the potential role of 2-deoxy-2-[(18)F]fluoro-D-glucose positron emission tomography (FDG-PET) (and tracers) and PET-computed tomography imaging in various benign disorders, particularly those related to thoracic structures. These various conditions can be broadly categorized into three groups: (a) infectious diseases (mycobacterial, fungal, bacterial infection), (b) active granulomatous disease such as sarcoidosis, and (c) other non-infectious/inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
0
39
0
1
Order By: Relevance
“…For many years, nuclear imaging using 67gallium (67Ga) has played an important role in the assessment of sarcoidosis (22). In recent years, 18F-FDG PET has been proposed to be a useful modality for the diagnosis and management of patients with inflammatory processes, particularly sarcoidosis (23,24). According to a previous review, whole-body 18F-FDG PET has been reported to be more sensitive than 67Ga scans for assessing the activity of sarcoidosis and demonstrates great value in detecting occult diagnostic biopsy sites (25).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, nuclear imaging using 67gallium (67Ga) has played an important role in the assessment of sarcoidosis (22). In recent years, 18F-FDG PET has been proposed to be a useful modality for the diagnosis and management of patients with inflammatory processes, particularly sarcoidosis (23,24). According to a previous review, whole-body 18F-FDG PET has been reported to be more sensitive than 67Ga scans for assessing the activity of sarcoidosis and demonstrates great value in detecting occult diagnostic biopsy sites (25).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a chronic systemic inflammatory disease of unknown origin involving preferentially lungs often with associated hilar and mediastinal adenopathy. Characteristic radiologic and PET features of thoracic sarcoidosis are well recognized by clinicians and imagers and are actually used to follow the status of patients undergoing treatment [15,16] .…”
Section: Inflammationmentioning
confidence: 99%
“…Un hypermétabolisme peut à la fois être constaté dans les infections mycobactériennes, ou bactériennes classiques, fongiques ainsi que dans les granulomatoses ( Fig. 3 et 4) au premier rang desquelles la sarcoïdose [9]. D'autres lésions bénignes peuvent apparaître avides au 18 F-FDG comme l'hamartome ( Fig.…”
Section: Les Lésions Bénignes Du Poumonunclassified